Brain dopamine neurone 'damage': methamphetamine users vs. Parkinson's disease – a critical assessment of the evidence. (5th September 2016) - Kish, Stephen J.; Boileau, Isabelle; Callaghan, Russell C.; Tong, Junchao
Abstract: The objective of this review is to evaluate the evidence that recreational methamphetamine exposure might damage dopamine neurones in human brain, as predicted by experimental animal findings. Brain dopamine marker data in methamphetamine users can now be compared with those in Parkinson's disease, for which the Oleh Hornykiewicz discovery in Vienna of a brain dopamine deficiency is established. Whereas all examined striatal (caudate and putamen) dopamine neuronal markers are decreased in Parkinson's disease, levels of only some (dopamine, dopamine transporter) but not others (dopamine metabolites, synthetic enzymes, vesicular monoamine transporter 2) are below normal in methamphetamine users. This suggests that loss of dopamine neurones might not be characteristic of methamphetamine exposure in at least some human drug users. In methamphetamine users, dopamine loss was more marked in caudate than in putamen, whereas in Parkinson's disease, the putamen is distinctly more affected. Substantia nigra loss of dopamine‐containing cell bodies is characteristic of Parkinson's disease, but similar neuropathological studies have yet to be conducted in methamphetamine users. Similarly, it is uncertain whether brain gliosis, a common feature of brain damage, occurs after methamphetamine exposure in humans. Preliminary epidemiological findings suggest that methamphetamine use might increase risk of subsequent development of Parkinson's disease. We conclude that the available literature is insufficient to indicate that recreational methamphetamine exposure likely causes loss of dopamine neurones in humans but does suggest presence of a striatal dopamine deficiency that, in principle, could be corrected by dopamine substitution medication if safety and subject selection considerations can be resolved. Abstract : Striatal dopamine (DA) marker changes in Parkinson's disease (PD) vs. methamphetamine (MA) users. In autopsied brain of persons with PD, striatal levels of all DA markers (DA and metabolites DOPAC, HVA and 3‐MT, synthesizing enzymes TH and AADC, and transporters VMAT2 and DAT) are low, whereas in MA users, only two markers (DA and DAT) are below normal. This suggests that any loss of brain dopamine neurones in at least a subgroup of recreational MA users, if at all present, might not be substantial.